Heavy Metals Leachability In Fly Ash Remediated Soil - Hollena, Anak Nori; Rafeah, binti Wahi; Kanakaraju, A/P Devagi; Dayang Norfadzila, Binti Awang Johari (Penerbit UMT, 2019)
This study focused on recycling fly ash, a by-product of power plants, to stabilize heavy metals in contaminated soil. Fly ash collected from the Sejingkat power plant in Kuching, Sarawak, was applied to soil from the roadside. The potential risk associated with the application of fly ash on the soil was assessed in terms of heavy metal concentration in leaching experiments. Deionized water and acidified water (deionized water acidified to pH 4.0 with nitric acid) were used as leaching agents and and passed through columns filled with untreated soil and soil-fly ash mixture (9:1). The Cd, Zn, Ni, Mn, Cu and Fe content in leachates were asessed at Day 0, 5, 10 and 15 after stabilization. Leacheate from the soil-fly ash mixture with acidified water had low pH range (4.5-6.2) compared to soil-fly ash mixture with deionized water (5.8-6.2), and this affected the solubility of heavy metals. The concentration of the metals in soil-fly ash mixture with acidified water leacheate was higher than soil-fly ash mixture with deionized water. In contrast, untreated soil did not show any clear pattern of heavy metal reduction except for Ni. Except for Cr, the concentrations of all the tested heavy metals in treated soil decreased with increasing pH as well as electrical conductivity from Day 0 to 15 of contact time. The results suggested that the solubility of heavy metals in soil leacheate was influenced by pH and the type of leaching agent. Therefore, the application of fly ash as a soil remediation agent may be a sustainable option to manage this by-product.